2016
DOI: 10.3389/fmicb.2016.01586
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Biomarkers for Tuberculosis: Evaluation of DOCK9. EPHA4, and NPC2 mRNA Expression in Peripheral Blood

Abstract: Lately, much effort has been made to find mRNA biomarkers for tuberculosis (TB) disease/infection with microarray-based approaches. In a pilot investigation, through RNA sequencing technology, we observed a prominent modulation of DOCK9, EPHA4, and NPC2 mRNA abundance in the blood of TB patients. To corroborate these findings, independent validations were performed in cohorts from different areas. Gene expression levels in blood were evaluated by quantitative real-time PCR (Brazil, n = 129) or reanalysis of pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 34 publications
2
45
0
1
Order By: Relevance
“…Eight [ 23 25 , 38 , 44 , 45 , 49 , 56 , 59 , 60 ] of the 18 studies evaluated signatures in populations with ODs. Only one study [ 43 ] made reference to blinding of the index test readers. Bias in patient selection arose in most studies due to case-control design and non-reporting of sampling method, resulting in a non-representative spectrum of patients.…”
Section: Resultsmentioning
confidence: 99%
“…Eight [ 23 25 , 38 , 44 , 45 , 49 , 56 , 59 , 60 ] of the 18 studies evaluated signatures in populations with ODs. Only one study [ 43 ] made reference to blinding of the index test readers. Bias in patient selection arose in most studies due to case-control design and non-reporting of sampling method, resulting in a non-representative spectrum of patients.…”
Section: Resultsmentioning
confidence: 99%
“…The differences in primary intended applications, which are reflected in the study populations used for biomarker discovery, may account for their inferior performance when evaluated solely for identification of incipient TB in a predominantly healthy, HIVnegative adult population. The signatures with inferior performance also included three discovered from panels of pre-selected candidate genes, rather than a genome-wide approach 15,28,33 , and four with only 6-24 TB cases in the discovery sets [32][33][34]38 . This suggests that using a genome-wide approach and including adequate numbers of diseased cases are important considerations during signature discovery.…”
Section: Eight Signatures Have Equivalent Diagnostic Accuracy For Incmentioning
confidence: 99%
“…The size of the nodes is proportional to the number of 26 downstream biomarkers associated with each regulator and the thickness of the edges is proportional to the -log10 P value for enrichment of each of the upstream 27 regulators. 28 38 space, stratified by months to disease. 39 Dashed lines represent positive predictive value planes, based on 2% pre-test probability.…”
Section: Figure 1 Genes Comprising the Top 8 Blood Transcriptomic Simentioning
confidence: 99%
“…1 A study conducted by Brazilian authors with participants aged > 18 years identified progression of 25.0% during the 1-year followup period. 23 Considering that children represent a risk group for TB progression, 7 it is expected that the rate of progression in this group would be even higher among our participants.…”
Section: Discussionmentioning
confidence: 94%